Genetically Modified Crops emerging scenario and detection strategies - Randhawa, Gurinder Jit; Singh, Monika (Indian Farming, 2015)
Genetically modified (GM) crops with desired traits have been developed by introducing gene or genetic construct of interest by using molecular or recombinant DNA techniques. These transgenic crops carry a new trait which was not present earlier in the native crop and thus the inserted transgene allows selection of transfomants and in enhancing the already existing trait. But there is need to allay the consumer concerns related to GM food products, before moving forward in introducing these crops in a big way.